2022
DOI: 10.3389/fmed.2021.771859
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Quadratus Lumborum Block for Pain Control in Patients Undergoing Hip Surgeries: A Systematic Review and Meta-Analysis

Abstract: BackgroundSeveral studies have reported the use of anterior, posterior and lateral quadratus lumborum block (QLB) for pain control in hip surgeries. However, high-quality evidence is lacking. The current review aimed to summarize data on the efficacy of QLB for pain control in patients undergoing hip surgeries.MethodsPubMed, Embase, and Google Scholar databases were searched up to August 5, 2021 for randomized controlled trials (RCTs) or non-RCTs assessing the efficacy of QLB for any type of hip surgery.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Wie bei allen interfaszialen Blockaden ist ein Erfolgselbst bei korrekter Ausbreitung des LAnicht sicher vorhersagbar. Trotz dieser Einschränkung zeigen fast alle randomisierten Studien eine effektive Schmerzunterdrückung für den AQLB von bis zu 48 h in der Hüftchirurgie, vergleichbar mit einer N.-femoralis-oder SIFI-Blockade [63,64,65]. Dagegen scheint die Quadrizepsschwäche weniger ausgeprägt.…”
Section: Anteriorer Quadratus-lumborum-blockunclassified
“…Wie bei allen interfaszialen Blockaden ist ein Erfolgselbst bei korrekter Ausbreitung des LAnicht sicher vorhersagbar. Trotz dieser Einschränkung zeigen fast alle randomisierten Studien eine effektive Schmerzunterdrückung für den AQLB von bis zu 48 h in der Hüftchirurgie, vergleichbar mit einer N.-femoralis-oder SIFI-Blockade [63,64,65]. Dagegen scheint die Quadrizepsschwäche weniger ausgeprägt.…”
Section: Anteriorer Quadratus-lumborum-blockunclassified
“…et al However, more recently, AQLB has increased popularity for use in THA [15][16][17][18]. In a meta-analysis of the efficacy of QLB for patients undergoing hip surgery, a significant reduction of 24 h total opioid utilization, reduced pain scores up to 48 h, and less postoperative nausea and vomiting was found in comparison to the control group [19]. However, the included studies did not analyze the effect of AQLB on ambulation or quadriceps strength.…”
Section: Key Pointsmentioning
confidence: 99%
“…Both transmuscular QLB and ESPB provide good postoperative pain control in hip surgeries, but QLB provides a better analgesic profile when compared to ESPB [34]. A recent systematic review and meta-analysis concluded that QLB reduced opioid consumption and pain scores in patients undergoing hip surgeries as a part of a multimodal analgesic regimen [35].…”
Section: Newer Regional Anaesthesia Techniques (Table-5) a Supraingui...mentioning
confidence: 99%